TOLERANCE LIMITS AND DETOXIFICATION MECHANISMS IN THE FISH TILAPIA MOSSAMBICA SUBJECTED TO AMMONIA TOXICITY - Chetty, C Sreeramulu; Naidu, R Chandramohan; Reddy, Y Sreenivasa; Aruna, P; Swami, K S (Indian Journal of Fisheries, 2011)
The effect of induced ammonia toxicity on selected enzyme systems ofcarbohydrate and nitrogen metabolism of freshwater fish, Tilapia mossambica wasstudied. An increas-s in lactate dehydrogenase (LI>H) and decrease in succinate(SDH) and malate dehydKjgenase activity levels were noticed in all the tissuesstudied. The activity levels of asparate aminotransferase (AAT) decreased in allthe tissues, while that of alanine aminotransferase (AlAT) had shown an increase.An elevation in the levels of Eirginasts activity and urea was found in the gill andliver tissues. The mettbolic sigmficance of these results is discussed